Etika Bisnis Digital Dalam Perspektif Ekonomi Syariah: Analisis Dark Pattern Pada Platform E-Commerce - Nia Kurnia Lestari; Iendy Zelviean Adhari (Paraduta : Jurnal Ekonomi dan Ilmu-Ilmu Sosial, 2026)
The rapid growth of e-commerce in Indonesia has accelerated digital economic expansion while introducing new ethical challenges, notably the spread of dark patterns: interface designs deliberately crafted to influence user decisions through hidden costs, fake urgency, fake scarcity, forced continuity, and confirmshaming. Research on this phenomenon remains dominated by Human-Computer Interaction, behavioral psychology, and consumer protection perspectives, while analyses grounded in fiqh muamalah (Islamic commercial jurisprudence) remain scarce. This study addresses that gap by developing an Islamic Ethical Evaluation Framework for Dark Patterns (IEEF-DP), mapping dark pattern practices onto the concepts of gharar (uncertainty), tadlis (concealment), ghubn fahisy (excessive exploitation), and taghrir (deception). Using a descriptive-analytical qualitative approach grounded in library research, the study applies qualitative content analysis combined with the interactive model of Miles and Huberman. Findings show hidden costs align with tadlis through concealment of material information, while fake urgency and fake scarcity relate to taghrir, gharar, and ghubn fahisy by creating false perceptions that pressure consumers into hasty decisions. Forced continuity potentially violates the principle of an taradhin (mutual consent), and confirmshaming shows conceptual affinity with ikrah ma'nawi (psychological coercion), warranting further empirical inquiry. The study culminates in the IEEF-DP, comprising four evaluative dimensions information transparency, factual accuracy, freedom of contract, and proportionality of harm providing a graduated, contextual basis for assessing the sharia compliance of digital interface design. The framework enriches digital business ethics literature from an Islamic economic perspective and offers conceptual guidance for regulators and e-commerce providers pursuing more transparent, equitable digital governance.